Espacios olvidados de la dignidad en tiempos de pandemia (REVISTA NODO, 2021)
This article aims to explore the forgotten spaces around human dignity that have been turning visible due to the irruption of COVID-19 in the global scene. According to its purpose, the research was based on epistemological references, in the current context, that would drive us to a New Perception of human dignity, in regard of solidarity values founded on female principles of self-care and life self-preservation.COVID-19 is a sign that reflects a global sickness developed in Western Civilization, at the same time is the result of rooted structural problems in a capitalist, patriarchal, dual, global system that attempted to kill life with the objective to reach a state of comfort supported in the unlimited consume of natural resources and the invisibilities of human dignity. During this crisis, social inequalities have started to seen more relevant. For this reason, it is important to understand that life begins at the territorial level in the objective of trying to implement alternatives substantiable strategies. In the last decade, the environmental and food crisis that affects the population with low income, can also increase the gap line between the being and no being realm, in terms of Grosfoguel (2011), due to the unilateral decisions of the capitalist countries that rule the world with politics that are against of the planet´s care and the democratic system of the being, those politics are driven by the patriarchal system, that have been increase its intensity.
Keywords: Pandemic; New feminisms; Alternatives strategies; Self-care; Education